Radial gradient of wood anatomical elements of Schinopsis quebracho-colorado (Schlecht.) Barkl. et Meyer, Anacardiaceae - Gimenez, Ana María (Bosque (Valdivia), 2000)
The aim of this study was to determine the radial gradient variation of wood elements of Schinopsis quebrachocolorado (Schlecht.) Barkl. et Meyer, in relation to age. The study was carried out on 10 individuals from Los Pilpintos, Copo Department, Santiago del Estero, Argentina. Healthy, well-formed trees with more than 30 cm diameter at breast height (DBH; 1.30 m) were selected from the dominant canopy, and wood samples were taken following the methodology of Helinska et al. 1991 and the terminology of IAWA. The anatomical variables selected were ring thickness, number of pores/mm2 , tangential pore diameter, net pore area/mm2 , type of pores, vessel and ray length, percentage of tissues, percentage of pore types, external and internal diameter of fibers, and fiber wall thickness. It was concluded that there was a radial gradient from pith to bark caused by cambial age, and the characteristics determining wood variability were ring thickness, number of pores/mm2 , vessel tangential diameter, net pore area and 3-4 multiple radial vessel proportion.